Automatic building rooftop extraction using a digital surface model derived from aerial stereo images. Issue 1 (2nd January 2022) - Wu, Bin; Wu, Siyuan; Li, Yong; Wu, Jianping; Huang, Yan; Chen, Zuoqi; Yu, Bailang
ABSTRACT: Automatic building rooftop extraction is of great importance to many applications including building reconstruction, solar energy supply, and disaster management. This study proposes a building rooftop extraction method using DSM data generated from aerial stereo images and vegetation cover vector data. The method consists of five steps: noise filtering, dilation reconstruction, vegetation and terrain region removal, region growing and merging, and post-processing. We applied the proposed method to the centre of Shanghai, China, a typical urban area. Experimental results show that the proposed method can successfully extract building rooftops, with an approximately 82.6% quality percentage and 96.2% matched overlay.